Pelatihan Aplikasi Program SPSS Bagi Dosen Program Studi Keperawatan Politeknik Nusa Utara: (Training of SPSS Program Aplications for Lecturers at Nursing Study Program in the Nusa Utara State Polytechnic) - Kekenusa, John Socrates; Hatidja, Djoni; Paendong, Marline Sofiana (Sam Ratulangi University, 2025)
SPSS Program Application Training for Lecturers of the North Nusa State Polytechnic Nursing Study Program has been carried out. This training aims to increase the knowledge and skills of the participants about statistics, especially about data analysis using SPSS computer software. The benefit of this activity is that the participants gain broader knowledge and insight into statistics, especially about research data analysis. The trainees are expected to understand more about statistics, so that they can improve the quality of research and teaching. Lecturers of the nursing study program at the Nusa Utara State Polytechnic, the qualification of knowledge about research data analysis is still relatively low. The lecturers were given knowledge about research methodology, especially data analysis using SPSS computer software.Facilitated by the guidebook and hands-on practice, the trainees followed enthusiastically, and all of them were able to practice the use of SPSS software in conducting data analysis, as well as draw conclusions from data analysis. ABSTRAK Pelatihan Aplikasi Program SPSS Bagi Dosen Program Studi Keperawatan Politeknik Negeri Nusa Utara telah dilaksanakan. Pelatihan ini bertujuan untuk menambah pengetahuan dan ketrampilan para peserta tentang statistika khususnya tentang analisis data menggunakan software komputer SPSS. Manfaat kegiatan ini ialah para peserta memperoleh pengetahuan dan wawasan yang lebih luas tentang statistika khususnya tentang analisis data penelitian. Para peserta pelatihan diharapkan lebih memahami tentang statistika, sehingga dapat meningkatkan kualitas penelitian dan pengajaran. Dosen program studi keperawatan Politeknik Negeri Nusa Utara, kualifikasi pengetahuan tentang analisis data penelitian masih relatif rendah. Para dosen diberi pengetahuan tentang metodologi penelitian, khususnya analisis data menggunakan software komputer SPSS. Dengan difasilitasi buku panduan serta praktek langsung, para peserta pelatihan mengikuti dengan penuh antusias, dan semuanya dapat mempraktekkan penggunaan software SPSS dalam melakukan analisis data, serta menarik simpulan hasil analisis data.